Efektivitas Aplikasi TikTok sebagai Media Sosial dalam Penyebaran Dakwah Islam di Era Digital - Alena Siti Maharani H; Anugrah Alifia Khairunnisa M; Cucu Surahman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of digital technology has brought changes in communication and information dissemination, including in Islamic preaching (dakwah). TikTok, as a short-video-based platform, has become one of the media used by preachers to convey Islamic messages in an engaging and interactive manner. This study aims to analyze the role of TikTok in the dissemination of Islamic preaching, assess its effectiveness, and identify the challenges and opportunities in its use. The research employs a quantitative approach by distributing questionnaires to respondents who actively use TikTok to access Islamic preaching content. The collected data is analyzed using pie chart diagram techniques to observe audience engagement patterns with Islamic preaching content on TikTok. The findings indicate that TikTok is highly effective in reaching a broader audience, especially the younger generation. However, challenges such as the ever-changing platform algorithm and potential misuse of features exist. The implication of this study is the need for a more adaptive and innovative preaching strategy to ensure optimal dissemination of Islamic messages. Future research is recommended to further explore audience engagement patterns and the long-term impact of digital preaching on social media.